LEAN E-HEALTH CARE: ITS PERFORMANCE IMPROVEMENT BASED ON BRAZILIAN UNIVERSITY HOSPITAL CASE STUDY - Maruyama, Úrsula; Braun, Leonardo Luiz; Stender, Gustavo; Martinez, Paloma; Reis, Augusto (Brazilian Journal of Operations & Production Management, 2016)
This paper aims to demonstrate how simple initiatives on public health sector are able to improve quality on service level. One of the most important aspects considered on this case study was the potential and motivation within University Hospital IT team to achieve excellence. Thus, management improvement started from quality management techniques applied by IT members to enhance results. This qualitative study case based on quality program deployed comparative analysis from literature to hospital IT management real initiatives. Results contribution demonstrate that inclusion and the development of collaborative workgroups can make difference to work environment and quality of service.